Synthesis of silver nanoparticles as a reagent for colorimetric detections of creatinine - Yusnaidar Yusnaidar; Martina Asti Rahayu; Yolanda Wulandari (Pascasarjana Universitas Negeri Medan, 2023)
In this study, Silver Nanoparticles (AgNPs) was synthesized using natrium citrate as a stabilizing agent and ascorbic acid as a reducing agent. The aim of this study is to investigate the optimum condition of creatinine colorimetric detection using silver nanoparticle synthesized. The reaction was carried out at temperature within an alkaline environment with a pH of 10,5. The concentration of reducing and capping agent showed a significant effect to absorption spectra via UV-Vis spectrophotometer. The produced citrate-capped AgNPs exhibited SPR absorbance within the range of 390–410 nm. The detection mechanism relies on the aggregtion of nanoparticles with analytes, resulting in a shift in Localized Surface Plasmon Resonance (LSPR) towards a longer wavelength. The experiment showed that the pH condition of the medium played an essential part in the interaction between creatinine and silver nanoparticles (AgNPs). Development of creatinine detection methods is based on the ability of tautomerization of creatinine to its anionic amino species at alkaline pH led to cross-linking with the negatively charged AgNPs through hydrogen bond networks, facilitating the aggregation mechanism. This aggregation resulted in particle resulted a color shift from yellow (with a maximum wavelength of 403nm) to dark blue (with a maximum wavelength of 670 nm) within 5 minute of reaction at pH 12. With this strategy, a linear relationship between the A670/A403 extinction ratio and creatinine concentrations was obtained in the range of 10–50μM with a coefficient of determination of 0.935.Keywords: Aggregation; Citrate; Creatinine; Silver nanoparticle; Surface plasmon